Supplementation of L-carnitine during in vitro maturation of mouse oocytes affects expression of genes involved in oocyte and embryo competence: An experimental study - Zohreh Zare; Beheshteh Abouhamzeh; Reza Masteri Farahani; Mohammad Salehi; Moslem Mohammadi (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Oocyte developmental competence is one of the key factors for determining the success rate of assisted reproductive technique. Objective: The aim of the current study was to investigate the effect of L-carnitine (LC) supplementation during in vitro maturation (IVM), on preimplantation embryo development and expression of genes involved in embryo competence derived from oocytes selected with brilliant cresyl blue (BCB) test. Materials and Methods: Cumulus-oocyte complexes (COCs) were obtained from NMRI mice ovaries. COCs were stained with BCB and then BCB+ (colored cytoplasm) oocytes cultured in IVM medium supplemented with 0.3 or 0.6 mg/ml LC. COCs untreated with LC were used as control. Fertilization rate and blastocyst development rate were determined after in vitro fertilization. In addition, quantitative reverse transcriptase polymerase chain reaction was used to measure relative genes expression related with development (Ccnb1, Mos, Ces5, and Dppa2) and apoptosis (Bax and Bcl-xL) in oocytes and embryos. Results: Oocytes treated with both LC concentrations showed higher blastocyst development rate compared with untreated oocytes (p<0.01). Moreover, fertilization rate was increased in oocytes treated with 0.6 mg/ml LC (p<0.01). Treatment of oocytes with both LC concentrations increased (p<0.01) the level of Ccnb1 mRNA in MII oocytes. The two-cell stage embryos and blastocysts derived from LC-treated oocytes (0.6 mg/ml) showed increased the expression levels of Dppa2 and Bcl-xl mRNA, respectively (p<0.01). Conclusion: The results of the present study show that adding of LC to the IVM medium of BCB+ oocytes can ameliorate reproductive success following in vitro fertilization.